A review on perovskite materials with solar cell prospective. (6th August 2021) - Ali, Nisar; Shehzad, Naeem; Uddin, Sarir; Ahmed, Rashid; Jabeen, Musarrat; Kalam, Abul; Al‐Sehemi, Abdullah G.; Alrobei, Hussein; Kanoun, Mohammed Benali; Khesro, Amir; Goumri‐Said, Souraya
Summary: Research on perovskite materials is an emerging trend from the last decade in order to improve the precision, stability, validity, consistency and reproducibility of reported perovskite materials and structures. These efforts are very much successful in advancing the composition, solvent, interface, and structure engineering leading toward the record efficiency value of 25.4%. However, the device instability has limited the practical applications of the hybrid perovskite solar cell. This review provides an up‐to‐date summary of the developments to resolve these issues with the uses of different synthesis routes and materials to obtain a stable ABX3 type structure of the perovskite materials. This review also comprehend the effects of electron transport layer on hysteresis phenomenon and long term stability with an outlook on current challenges and further development. Furthermore, a comprehensive discussion on the crystal structure, energy level, absorption coefficient, degradation and chemical bonding in perovskite solar cell materials is also included. Finally, a brief future outlook for perovskites solar cells is discussed. Abstract : The big question mark on perovskite solar cells is it is stability to mositure. We are suggesting that the stability can be improved by using an absorbent material as a capping layer around the solar cell in the form of thin‐flim that any moisture may get absorbed and may not penetrate inside the material.